1980
DOI: 10.1161/01.res.46.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Renal receptors in the rat sensitive to chemical alterations of their environment.

Abstract: SUMMARY Two major groups of renal chemosensory neural elements have been identified in the rat: one specifically activated by renal ischemia, the previously described "R" chemoreceptors, and the other by backflow of nondiuretic urine into the renal pelvis. The latter group is the object of the present investigation. In anesthetized, male Sprague-Dawley rats, single-unit recordings were obtained by dissection of the centrally cut nerves of the right kidney. The responses of single units to backflow into the ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 30 publications
4
59
2
Order By: Relevance
“…[11][12][13][14]31 The reason for the discrepancy between our result and other studies is not clear. However, the present study also showed that blood pressure and RSNA were consistently increased in response to elevated pelvic pressure in the contralaterally nephrectomized rats.…”
Section: Wky Rats Shrscontrasting
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14]31 The reason for the discrepancy between our result and other studies is not clear. However, the present study also showed that blood pressure and RSNA were consistently increased in response to elevated pelvic pressure in the contralaterally nephrectomized rats.…”
Section: Wky Rats Shrscontrasting
confidence: 99%
“…It has been considered that the ARN activity is increased by stimulation of the sensory receptors in the kidney. And as the sensory receptors near the pelvic wall are distinctively sensitized to changes in the pelvic pressure [11][12][13] or backflow of the urine into the pelvis, 14 elevation of the pelvic pressure has been a useful tool to activate ARNs. [11][12][13] …”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of afferent renal nerves has been shown to evoke alterations in sympathetic nerve activity and arterial blood pressure (31,44). The excitatory influence may represent an activation of quiescent renal afferents in response to a variety of stimuli (35,36). There are multiple triggers in the HF condition that have the potential for increased activation of the renal afferent nerve activity, including reduced perfusion pressure, increased venous pressure, increased inflammation, and increased oxidative stress to name a few (18).…”
Section: Discussionmentioning
confidence: 99%
“…Similar conflicting evidence exists for other species (Aars and Akre, 1970;Ueda et al, 1967b;Beacham and Kunze, 1969;Calaresu et al, 1976Calaresu et al, , 1978. Such variations may, in part, reflect stimulation of mixed afferent popula-tions, since there is now clear evidence that the renal nerves contain a heterogeneous group of mechanoand chemoreceptor afferent fibers (Calaresu et al, 1978;Recordati et al, 1980).…”
mentioning
confidence: 86%